A web application for post-processing seismic hazard assessment results - Alvarez, Leonardo; Lindholm, Conrad (Nexo Revista Científica, 2024)
A web application for post-processing of PSHA results in order to obtain a variety of maps and graphics for user-defined needs is discussed. It was developed for using the results from the R-CRISIS software main calculations, but its principles are universal and may be adapted for any other PSHA software. The process is performed in two steps: the first is to prepare files to be used as input for the web application, and the second step consists of processing these files for new results and plots (trough the execution of programs and scripts). The work is organized in a server-client scheme, where the server side has all the required software together with the results and input files from the PSHA calculation. The software is accessed through a Web-Portal on the server side. We present examples of requests and results.